An Examination of Gamification Elements and Apps in Teaching & Learning - Rajendran, Dineshkumar; Santhanam, Prasanna (International Journal of Psychosocial Rehabilitation, 2020)
Gamification is implementing game elements in non-game environments to increase motivation. [1], [2]. Education is one such domain where gamification has proven its potential by maximizing the motivation among students. In this paper, we carefully selected and analyzed 15 journals from the existing gamification articles in the education domain that were published from the years 2013-2020. The apps and game elements used for gamification were further weighed and highlighted the gaps. This journal also offers insights on the future development of gamification in the education domain.